POTENSI BIJI LAMTORO GUNG DAN BIJI KEDELAI SEBAGAI BAHAN BAKU PEMBUATAN TEMPE KOMPLEMENTASI - Sayudi, Slamet; Herawati, Netti; Ali, Akhyar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This study aim was to evaluate the content of tempeh complementation from leucaena seed and soybean have been met quality standards tempeh (SNI 01-3144-2009) and in terms of acceptable organoleptic assessment by panelists.. This research used Complete Randomized Design (CRD) with six treatment that is: L1K1 (100% soybean), L2K2 (20% leucaena seed : 80% soybean), L3K3 (40% leucaena seed : 60% soybean), L4K4 (60% leucaena seed : 40% soybean), L5K5 (80% leucaena seed : 20% soybean) and L6K6 (100% leucaena seed). The results show that the complementation of leucaena seed and soybean significantly affected the moisture, ash, protein, and crude fiber. The tempeh complementation have been met quality standards tempeh (SNI 01-3144-2009). Show that the treatment affected moisture, ash, protein, crude fiber contents. Leucaena seed and soybean complementation L4K4 (60% leucaena seed : 40% soybean) was the seleceted tempeh with moisture 61.248%, ash 0.891%, protein 20.491% and crude fiber 2.183% and in terms of acceptable organoleptic assessment by panelists. Keywords : Leucaena seed, soybean, tempeh, fermentation, Rhizopus sp.